LANKESTER CATALOGUE OF COSTA RICAN ORCHIDACEAE - Pupulin, Franco (2026)
This study presents an updated comprehensive catalogue of the Costa Rican orchid flora. We have documented 1684 species, four subspecies, 14 natural hybrids, and seven forms across 201 genera and two nothogenera, × Bensteinia and × Cochlezella. All Orchidaceae subfamilies are represented except for Apostasioideae. The subtribe Pleurothallidinae accounts for about 35% of all the species, followed by Laeliinae (20%) and Oncidiinae (+12%). The most species-rich genera in Costa Rica are Epidendrum (245 spp.), Lepanthes (163 spp.), Stelis (109 spp.), and Pleurothallis (63 spp.). About 30% of all the species are endemic, primarily concentrated in Lepanthes (109 spp. = 67%), Epidendrum (76 spp. = 31%), Stelis (40 spp. = 37%), Telipogon (35 spp. = 88%), and Pleurothallis (31 spp. = 46%). All species are vouchered by specimens housed in major public herbaria, including CR, JBL, and USJ in Costa Rica, as well as AMES, K, SEL, US, and W, on the international scale, among others. The catalogue includes 5300 orchid names at the specific and subspecific ranks, nearly 70% of which are treated as synonyms. The new catalog presents an increase of 324 species compared to its predecessor, published twenty years ago, a net increment of almost 24%. The rise in the recorded richness of the Costa Rican orchid flora is mainly attributed to the discovery of species new to science and a lesser extent, taxa newly recorded for the country as the result of the systematic explorations carried out in Costa Rica during the present century. A phylogenetic arrangement of the genera recorded in Costa Rica, from the rank of subfamily to that of subtribe, is presented, including a synopsis of the diversity recorded for each genus. An enumerated checklist of the accepted species and a comprehensive index of accepted names and synonyms are also provided. The index is cross-referenced with both the checklist and the main catalogue. New combinations for Andreettaea fimbriata and Camaridium muscoides are proposed. Photographs of representative species from the majority of genera, based on Costa Rican vouchers, are included. We expect that this catalogue will inspire orchidological and botanical research in Costa Rica and other Neotropical regions, leading to additional discoveries in the upcoming years